A SYNOPSIS OF THE GENUS COLUTEA (FABACEAE) IN IRAN. (24th February 2014) - Pooyan, P.; Ghahremaninejad, F.; Assadi, M.
<x content-type="archive" xml:space="preserve">Abstract</x> The genus Colutea (Fabaceae) has been revised in preparation for the Flora of Iran treatment and a synopsis is presented here. In Iran the genus includes four sections, three subsections and nine species. An identification key, notes and distributions are given for the taxa. Two new subsections are described: Colutea sect. Rostrata subsect. Gifana and Colutea sect. Rostrata subsect. Uniflora.